Features of micro- and ultrastructure of low-fat butter and its low-fat analogues - E. V. Topnikova; E. N. Pirogova; Yu. V. Nikitina; T. A. Pavlova (Пищевые системы)
The aim of the research was to study the features of the structure of low-fat butter and butter pastes, which, in terms of composition and properties, more fully meet the requirements of a healthy diet than high-fat types of butter. The objects of research were: butter with fat content of 72.5%; butter with fat content of 55% made with the addition of skimmed milk powder; butter of the same fat content with the addition of stabilizers based on guar and xanthan gums and emulsifiers based on monoand diglycerides of fatty acids; butter pastes with fat content of 45% with similar additives used to increase the stability of the process of butter formation and improve the texture. The microstructure was studied using an MBI-6 microscope, and the ultramicrostructure was studied using a Phillips electron microscope. In the first case, the sample was prepared by crushing the sample, in the second one — by the method of ultrafast freeze-fracture and etching. Researches have shown that the use of the introduced ingredients improves the homogeneity of the structure of the studied products. Due to the ability of milk proteins and stabilizers to retain moisture, it is more evenly distributed and well retained in the fat matrix of the product, formed from crystalline and liquid fat in the form of a continuous phase, which is confirmed by a sufficient penetration depth of the fat-soluble dye. Plasma droplets in butter with fat content of 72.5% and 55% are more isolated than in butter pastes, as indicated by the greater penetration depth of the water-soluble dye. The average diameter of isolated moisture droplets in low-fat products was 3.3–5.4 μm, and the average diameter of the fat globules that form the basis of the crystalline framework was 5.4–7.4 μm, depending on the composition of the product. For butter with fat content of 72.5%, the values of these indicators were 2.8 and 4.0 μm. The results of the study indicate the presence of differences in the sizes of structural elements, but at the same time confirm the uniformity of the structure of low-fat products, allowing them to be attributed to dispersions «water-in-oil».